Formation of nucleobases in a Miller-Urey reducing atmosphere - Ferus, Martin; Pietrucci, Fabio; Saitta, Antonino Marco; Knížek, Antonín; Kubelík, Petr; Ivanek, Ondřej; Shestivska, Violetta; Civiš, Svatopluk (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The Miller-Urey experiments pioneered modern research on the molecular origins of life, but their actual relevance in this field was later questioned because the gas mixture used in their research is considered too reducing with respect to the most accepted hypotheses for the conditions on primordial Earth. In particular, the production of only amino acids has been taken as evidence of the limited relevance of the results. Here, we report an experimental work, combined with state-of-the-art computational methods, in which both electric discharge and laser-driven plasma impact simulations were carried out in a reducing atmosphere containing NH3 + CO. We show that RNA nucleobases are synthesized in these experiments, strongly supporting the possibility of the emergence of biologically relevant molecules in a reducing atmosphere. The reconstructed synthetic pathways indicate that small radicals and formamide play a crucial role, in agreement with a number of recent experimental and theoretical results.
Keywords: Origin of Life; Carbon Monoxide; asteroid impact; Ammonia; Models, Chemical; původ života; Evolution, Chemical; reducing atmosphere; life origins; oxidace-redukce; RNA; amoniak; evoluce chemická; atmosféra; Formamides; formamidy; Atmosphere; Oxidation-Reduction; chemické modely; oxid uhelnatý